PENGARUH CUSTOMER EXPECTATION, TRUST, SERVICE QUALITY, DAN PERCEIVED VALUE TERHADAP CUSTOMER SATISFACTION SERTA DAMPAKNYA TERHADAP REPURCHASE INTENTION PADA PENGGUNA LAYANAN O2O MAKANAN DI INDONESIA - Nurvinka, Afsari Zulsi; Kurniawati, Kurniawati (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
The rapid growth of digital transformation has accelerated the development of online-to-offline (O2O) food delivery services in Indonesia, particularly in the post-pandemic period, leading to significant shifts in consumer behavior. Consumers increasingly demand not only convenience but also high service quality, reliability, and digital security. In an increasingly competitive market, understanding the determinants of customer satisfaction is essential for sustaining business performance and encouraging repeat purchases. This study aims to examine the effects of customer expectation, trust, service quality, and perceived value on customer satisfaction, as well as the impact of customer satisfaction on repurchase intention in O2O food services. Employing the Stimulus-Organism-Response (SOR) framework, data were collected through a survey of active users of O2O food platforms such as GoFood, GrabFood, and ShopeeFood in Indonesia. The findings indicate that trust and service quality positively influence customer satisfaction, while customer expectation and perceived value do not have a significant effect. Furthermore, customer satisfaction is found to have a positive impact on repurchase intention. The strategic implications of this study highlight the importance of organizational policies focused on strengthening customer trust through enhanced data security, information transparency, and consistent service quality. Additionally, O2O platform providers are encouraged to prioritize comprehensive user experience improvements to foster sustained customer satisfaction and long-term loyalty.